Synthesis of bile acid dimers linked with 1,2,3-triazole ring at C-3, C-11, and C-24 positions - Aher, Nilkanth G.; Pore, VS (Synlett, 2005)
1,3-Dipolar cycloaddition of propargyl ester of a bile acid to an azide group attached at different positions of another bile acid gave three new 1,2,3-triazole-containing dimeric analogues in excellent yields.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; Bile acids; Click chemistry; steroidal dimers

Design and synthesis of fluconazole/bile acid conjugate using click reaction - Pore, Vandana S.; Aher, Nilkanth G.; Kumar, Manish; Shukla, Praveen K. (Tetrahedron, 2006)
Novel fluconazole/bile acid conjugates were designed and their regioselective synthesis was achieved in very high yield via Cu(I) catalyzed intermolecular 1,3-dipolar cycloaddition. These new molecules showed good antifungal activity against Candida species. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Click chemistry; fluconazole/bile acid conjugate

Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Synthesis and antifungal activity of 1,2,3-triazole containing fluconazole analogues - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Kumar, Awanit; Shukla, Praveen K.; Sharma, Aanchal; Bhat, Manoj K. (Bioorganic & Medicinal Chemistry Letters, 2009)
Fluconazole based novel mimics containing 1,2,3-triazole were designed and synthesized as antifungal agents. Their antifungal activities were evaluated in vitro by measuring the minimal inhibitory concentrations (MICs). Compounds 12, 15, and 16 were found to be more potent against Candida fungal pathogens than control drugs fluconazole and amphotericin B. The studies presented here provide structural modi. cation of fluconazole to give 1,2,3-trazole containing molecules. Furthermore, these molecules were evaluated in vivo against Candida albicans intravenous challenge in Swiss mice and antiproliferative activities were tested against human hepatocellular carcinoma Hep3B and human epithelial carcinoma A431. It was found that compound 12 resulted in 97.4% reduction in fungal load in mice and did not show any profound proliferative effect at lower dose (0.001 mg/ml). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Conjugates; Fluconazole

Synthesis and biological evaluation of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives via click chemistry approach - Kategaonkar, Amol H.; Shinde, Pravin V.; Kategaonkar, Atul H.; Pasale, Sharad K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (European Journal of Medicinal Chemistry, 2010)
Synthesis of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives (4a-h) using 1,3-dipolar cycloaddition (click chemistry) reaction of 3-(azidomethyl)-2-chloro-quinoline derivatives (3a-h) with phenyl acetylene in the presence of Cu(I) catalyst has been achieved in very high yield. These molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 2; 2-Chloro3-formyl quinoline; 3-Triazole; Antibacterial; antifungal; Click chemistry

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis and biological evaluation of new 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Nawale, Laxman; Sarkar, Dhiman (Research on Chemical Intermediates, 2018)
A series of 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives (8a-p) have been synthesized. The structure of the newly synthesized compounds was determined by spectral analysis. The title compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Further, the synthesized compounds were screened for antimicrobial activity against standard Gram-negative bacteria Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059) and Gram-positive bacteria Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162). Among all the synthesized compounds, 8a-c, f-h, m exhibited good activity against dormant M. bovis BCG strain. Compounds 8h, j exhibited good activity against all tested bacterial strains. All active compounds were screened for cytotoxicity and found inactive. Their high potency and promising antimycobacterial activity suggest that these compounds could serve as good leads for further optimization and development.
Keywords: 1; 2; 3-Triazole; antibacterial activity; Antitubercular activity; Thiazole

Synthesis and antimycobacterial evaluation of new 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Chakraborty, Shakti; Choudhari, Amit; Phalle, Siddharth; Choudhari, Prafulla; Sarkar, Dhiman (Medicinal Chemistry Research, 2019)
A new series of 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives, 6a-w have been synthesized by click reaction of substituted benzylazide, 5a-d with 5-ethynyl-4-methyl-2-substituted phenylthiazole, 4a-f. The starting compounds 4-ethynyl-2-substituted phenylthiazole (4a-f) were synthesized from the corresponding thiazole aldehyde by using the Ohira-Bestmann reagent. The structure of the synthesized compounds was determined by spectral analysis. All the synthesized compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177). Most of the synthesized compounds reported good activity against M. tuberculosis H37Ra strain with IC50 range of 0.58-8.23 mu g/mL. Compounds 6g and 6k reported good antitubercular activity with MIC90 values of 4.71 and 2.22 mu g/mL, respectively. Potential antimycobacterial activity suggested that these compounds could serve as good lead compounds for further optimization and development of a newer antitubercular candidate. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; Antitubercular activity; Molecular docking; Ohira-Bestmann reagent; Thiazole

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study

4-aminoantipyrine linked bis-1,2,3-triazole based probes for Cu(II) sensing - Lal, Bajrang; Kumar, Sachin; Tittal, Ram Kumar; Singh, Gurleen; Singh, Jandeep; Ghule, Vikas D.; Mathpati, Ramling S.; Sabane, Jagjivan K. (Journal of Molecular Structure, 2024)
Herein, two molecular probes of 4-aminoantipyrine-linked bis-1,2,3-triazoles have been studied for metal ion sensing applications. The crystal structure of one of the probes named as 4,4 `-((4,4 `-(((1,5-dimethyl- 3- oxo- 2- phenyl- 2,3- dihydro- 1H- pyrazol- 4-yl) azanediyl) bis(methylene))bis(1H-1,2,3-triazole-4,1-diyl))bis(methylene))dibenzonit rile (3b) crystalizes in Monoclinic crystal system in P 1 21/n 1 space group. Both probes responded more strongly and selectively to Cu(II) than other tested metal ions (K+, Na+, Mg2+, Ba2+, Ca2+, Cr3+, Mn2+, Co2+, Zn2+, Cd2+, Ni2+, Hg2+, and Pb2+). Job's plot suggested a 1:1 stoichiometric ratio of ligand and metal ion. Both probes showed an association constant of 2.48 x 10(3) M-1 and 3.73 x 10(3) M-1 through Benesi-Hildebrand (B-H) plot. The geometries of both probes and their complexes were optimized by DFT using B3LYP/6-311 G(d,p) and B3LYP/LanL2DZ basis sets, and properties were supported by Mulliken atomic charge and Molecular electrostatic potential. Molecular docking on both probes and their complexes with Type-II topoisomerases(PDB ID: 4G0V) protein was conducted to foretastes anticancer activity.
Keywords: 2; 3-Triazole; 4-aminoantipyrine; and Molecular docking; Bis-1; Cu2+ Sensor; DFT; X-ray crystallography